Bathroom battlegrounds : how public restrooms shape the gender order - Davis, Alexander K., 1988- (University of California Press, 2020)
"Today's debates about transgender inclusion and public restrooms may seem unmistakably contemporary, but they have a surprisingly long and storied history in the United States-one that concerns more than mere "potty politics." Alexander K. Davis takes readers behind the scenes of two hundred years' worth of conflicts over the existence, separation, and equity of gendered public restrooms, documenting at each step how bathrooms have been entangled with bigger cultural matters: the importance of the public good, the reach of institutional inclusion, the nature of gender difference, and, above all, the myriad privileges of social status. Chronicling the debut of nineteenth-century "comfort stations," twentieth-century mandates requiring separate-but-equal men's and women's rooms, and twenty-first-century uproar over laws like North Carolina's "bathroom bill," Davis reveals how public restrooms are far from marginal or unimportant social spaces. Instead, they are-and always have been-consequential sites in which ideology, institutions, and inequality collide"--